Legal Analysis of the Use of Medical Marijuana Against Indonesian Citizens Undergoing Marijuana Treatment Outside Indonesia - Kemal Alfaridzi; Pudji Astuti (NOVUM : JURNAL HUKUM, 2026)
This study aims to analyze the regulatory framework governing discipline for Government Employees with Work Agreements (PPPK) as specified in Law Number 20 of 2023 concerning the State Civil Apparatus (ASN), and to examine future regulatory directions to ensure legal certainty in the enforcement of discipline across all civil servants. The research adopts a normative juridical method with a statutory approach by reviewing relevant laws and legal doctrines. Data were collected through literature studies involving primary, secondary, and non-legal materials, and analyzed using a prescriptive method to provide normative arguments and a legal perspective on the issues observed. The findings indicate that disciplinary enforcement for PPPK currently relies on general provisions in the ASN Law of 2023, without comprehensive technical guidelines. In practice, most procedures still refer mutatis mutandis to Government Regulation Number 94 of 2021, which was originally intended for civil servants (PNS). This creates a legal vacuum that may lead to uncertainty and inconsistency in disciplinary enforcement. Therefore, a regulatory update specifically addressing PPPK is urgently needed to uphold the principles of justice, legal certainty, and equality within the national civil service system.